Hubungan Kelincahan dengan Kemampuan Dribbling pada Siswa Ekstrakurikuler Bola Basket - Adika Fatahillah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the presence or absence of agility relationship with dribbling ability. Samples in this study only male students amounted to 20 people, the sampling technique is done by purposive sampling. This research method pertained to the type of quantitative research by using correlational analysis techniques. The data collection technique uses the Illinois Agility Run agility test instrument and dribbling ability with a dribbling bolabasket ability test. The results obtained tcount greater than ttable or 3.6977 greater than 1.734, so it can be said that the hypothesis Ha accepted research and hypothesis H0 rejected . Can be seen from the calculation of results that show the value of correlation r with the provision value r = 0.657 then the correlation coefficient pertained strong. The result of coefficient value showed that the variables of free agility contribute to the ability of dribblingbolabasket of 43.16 percent and the remaining 56.84 percent is determined by other variables Keywords: Agility, Dribbling Capability